RESEÑA de: Martínez Cantón, Clara Isabel. El ritmo como clave del verso en Antonio Colinas. León : Universidad de León, 2013. - Polo Cano, Nuria (Signa: Revista de la Asociación Española de Semiótica, 2014)
-